ETIKA GURU MENURUT KH. HASYIM ASY’ARI DALAM KITAB AADABUL ‘AALIM WAL MUTA’ALLIM - Nabil, Muhammad Arif Nasruddin, Salim (JIPI (Jurnal Ilmiah Pendidikan Islam), 2024)
In education, educators or teachers have the task of providing information or knowledge and providing examples of good behavior for their students. KH. Hasyim Asy'ari in his book entitled Aadaabul 'Aalim wal Muta'allim gives instructions to teachers so they can become exemplary educators. This study aims to find out how teacher ethics and how the concept of teacher ethics according to KH. Hasyim Asy'ari in the book Aadaabul 'Aalim wal Muta'alim which is then expected to be useful as a reference for teachers so they can maintain good attitudes, ethics and behavior. The research method used is the library research method (library). The data collected came from books, journal articles, and other supporting sources, with the primary data being the book Aadaabul 'Aalim wal Muta'allim, by KH. Hasyim Ash'ari. The data collected through the documentation method was then analyzed using the content analysis method. The results of the study show that in the book Aadaabul 'Aalim wal Muta'allim the ethics of a teacher is divided into three, namely, the ethics of the teacher towards himself, the ethics of the teacher towards his lesson, the ethics of the teacher towards students. In everyday life, not only students are required to have good ethics, a teacher also has an obligation to be ethical in all aspects, because the teacher is a direct example that is seen by his students.